2002
DOI: 10.1007/s10350-004-6392-9
|View full text |Cite
|
Sign up to set email alerts
|

A Study to Determine the Nitroglycerin Ointment Dose and Dosing Interval That Best Promote the Healing of Chronic Anal Fissures

Abstract: Nitroglycerin ointment did not alter healing but significantly and rapidly reduced the pain associated with chronic anal fissures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
2
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 37 publications
2
45
2
4
Order By: Relevance
“…In our study, 15 patients (14.6 %) discontinued the treatment because of headache (12.6 %) and local discomfort (2 %). This percentage is similar to other studies that used different GTN concentration [25][26][27].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 15 patients (14.6 %) discontinued the treatment because of headache (12.6 %) and local discomfort (2 %). This percentage is similar to other studies that used different GTN concentration [25][26][27].…”
Section: Discussionsupporting
confidence: 90%
“…Psyllium may have exerted its effect by preventing the formation of hard stool causing mechanical trauma responsible for the development of chronic anal fissure and diarrheal attacks. Recent studies have emphasized that topical nitroglicerin at 0.04% concentration 2×1.5 mg is the most efficient dose in treatment of chronic anal fissure [28,29]. In a study carried out by Ergun et al [30] on 568 pharmacists, it was shown that only 24 (%4) of the pharmacists prepared topical nitroglicerin prescription and %0.4 nitroglicerin content was not found exactly at this ratio in preparations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, up to 20% of patients cease GTN therapy due to the severity of their headaches. [30], [31], [32], [33] A 2%GTN ointment applied twice to the anoderm for 6 weeks results in a complete healing in 98% of patients. [6] In another study, Topical diltiazem ointment was used as an agent for chemical sphincterotomy for chronic anal fissure.…”
Section: Topical Nitratesmentioning
confidence: 99%
“…[31] Nonetheless, lateral internal sphincterotomy still stands as the surgical treatment of choice for refractory anal fissures and may be offered without pharmacologic treatment failure according to the practice parameters by the American Society of Colon and Rectal Surgeons. [8] Reports of sphincterotomy for various anal pathologies probably date back to the 1700s.…”
Section: Division Of Internal Anal Sphinctermentioning
confidence: 99%